Synergistic Effect of Nitazoxanide with Neuraminidase Inhibitors against Influenza A Viruses In Vitro - Belardo, Giuseppe (Antimicrob Agents Chemother, 2015)
The emergence of drug-resistant influenza A virus (IAV) strains represents a serious threat to global human health and underscores the need for novel approaches to anti-influenza chemotherapy. Combination therapy with drugs affecting different IAV targets represents an attractive option for influenza treatment. We have previously shown that the thiazolide anti-infective nitazoxanide (NTZ) inhibits H1N1 IAV replication by selectively blocking viral hemagglutinin maturation. Herein we investigate the anti-influenza activity of NTZ against a wide range of human and avian IAVs (H1N1, H3N2, H5N9, H7N1), including amantadine-resistant and oseltamivir-resistant strains, in vitro. We also investigate whether therapy with NTZ in combination with the neuraminidase inhibitors oseltamivir and zanamivir exerts synergistic, additive, or antagonistic antiviral effects against influenza viruses. NTZ was effective against all IAVs tested, with 50% inhibitory concentrations (IC(50)s) ranging from 0.9 to 3.2 μM, and selectivity indexes (SIs) ranging from >50 to >160, depending on the strain and the multiplicity of infection (MOI). Combination therapy studies were performed in cell culture-based assays using A/Puerto Rico/8/1934 (H1N1), A/WSN/1933 (H1N1), or avian A/chicken/Italy/9097/1997 (H5N9) IAVs; dose-effect analysis and synergism/antagonism quantification were performed using isobologram analysis according to the Chou-Talalay method. Combination index (CI) analysis indicated that NTZ and oseltamivir combination treatment was synergistic against A/Puerto Rico/8/1934 (H1N1) and A/WSN/1933 (H1N1) IAVs, with CI values ranging between 0.39 and 0.63, independently of the MOI used. Similar results were obtained when NTZ was administered in combination with zanamivir (CI = 0.3 to 0.48). NTZ-oseltamivir combination treatment was synergistic also against the avian A/chicken/Italy/9097/1997 (H5N9) IAV (CI = 0.18 to 0.31). Taken together, the results suggest that regimens that combine neuraminidase inhibitors and nitazoxanide exert synergistic anti-influenza effects.